2007
DOI: 10.1007/s00464-006-9165-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes confirm the superior efficacy of extended Heller myotomy with Toupet fundoplication for achalasia

Abstract: For the treatment of achalasia, EM with Toupet fundoplication provides excellent durable dysphagia relief that is superior to SM with Dor fundoplication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(67 citation statements)
references
References 21 publications
(21 reference statements)
1
66
0
Order By: Relevance
“…There are no published data comparing both. Some surgeons prefer a posterior approach as it keeps the edges of the myotomy separated and it may be more effective for antireflux operation while others prefer an anterior method and say it is easier to perform without the need of posterior dissection and it adds the advantage of covering the exposed mucosa (3,(7)(8)(9)(10). In our study group we mostly preferred to perform a Laparoscopic Heller myotomy with Toupet fundoplication (34 patients) as it is suggested in many reports (10).…”
Section: Discussionmentioning
confidence: 99%
“…There are no published data comparing both. Some surgeons prefer a posterior approach as it keeps the edges of the myotomy separated and it may be more effective for antireflux operation while others prefer an anterior method and say it is easier to perform without the need of posterior dissection and it adds the advantage of covering the exposed mucosa (3,(7)(8)(9)(10). In our study group we mostly preferred to perform a Laparoscopic Heller myotomy with Toupet fundoplication (34 patients) as it is suggested in many reports (10).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the vast majority (86%) rated the operation as successful. We credit the good results to our adherence to the surgical principles of complete diverticulum resection, relief of distal obstruction with a myotomy, and when possible, mitigate the risk of gastroesophageal reflux with a 270-degree posterior fundoplication [21]. No studies have compared the long-term outcomes in patients operated from the chest and the abdomen for epiphrenic diverticula.…”
Section: Symptomatic Outcomesmentioning
confidence: 99%
“…They found that extended myotomy provides excellent dysphagia relief, superior to that obtained with standard myotomy. 25) Patti et al reported that impaired visualization of the gastroesophageal junction might be the principal cause of an inadequate cardiomyotomy. 26) Available evidence thus indicates that evaluation of the anterior esophageal fat pad to accurately identify the gastroesophageal junction and a cut length of at least 2 cm in cardiomyotomy are the most important determinants of a successful outcome of Heller myotomy (Fig.…”
Section: Heller Myotomymentioning
confidence: 99%